Pressure and boundary layer measurements on a tapered swept wing in flight - Hyde, D. (College of Aeronautics, 1960)
Pressure and boundary layer measurements were made in flight on a full scale swept half-wing mounted as a dorsal fin on the mid fuselage of an. Avro Lancaster aircraft. A Reynolds Number range of 0.88 x 106 to 1.86 x 106 per foot was available. The tapered wing had a semi-span of 102.5 ins. and an aspect ratio of 2.87; the quarter chord sweep was 40o and the symmetrical section was RAE 102, of 8% thickness/chord ratio along wind. Comprehensive static pressure measurements were recorded over a nominal incidence range of 0o to 10o. At mid semi-span and zero incidence, the measured chordwise pressure distribution compared well with theory. The non-dimensional chordwise and spanwise loadings were in close agreement with Kuchemann' s predictions, but the experimental lift curve slope was 6% greater than the theoretical value. From the boundary layer results the positions of the transition fronts were deduced. No laminar flow was obtained on either surface at the highest Reynolds number of 1.86 x 106 per foot, or at incidences of 6° and greater at all test Reynolds numbers. The secondary flow Reynolds number corresponding to the onset of sweep instability was found to be in the range 80 < N < 133; Owen's predicted critical value is 125.